2016
DOI: 10.1016/j.amjmed.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Cardiorespiratory Fitness Within an Obesity Risk Classification Model Identifies Men at Increased Risk of All-Cause Mortality

Abstract: Background: Guidelines for identification of obesity-related risk stratify disease risk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Similarly, the rise of AUROC for HTN and DM were larger than DLP and MetS, which might be due to the fact that DLP and MetS were primarily influenced by abdominal obesity; while HTN and DM also depended on the amount of fat to some extent. In addition, BMI and WC were the preferable combinations in general, which was in agreement with Zhu et al’s and Ricketts et al ’ s study [40,42]. Besides, the AUROC of younger age groups was the largest in most cases, which implied that obesity might have much more impact on young people.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, the rise of AUROC for HTN and DM were larger than DLP and MetS, which might be due to the fact that DLP and MetS were primarily influenced by abdominal obesity; while HTN and DM also depended on the amount of fat to some extent. In addition, BMI and WC were the preferable combinations in general, which was in agreement with Zhu et al’s and Ricketts et al ’ s study [40,42]. Besides, the AUROC of younger age groups was the largest in most cases, which implied that obesity might have much more impact on young people.…”
Section: Discussionsupporting
confidence: 89%
“…Firstly, the definition of MetS had an overlap with WC, which might lead to overestimations of adjusted AUROC and ORs for MetS. Secondly, age was adjusted in our studies; however, other confounders that might have impact on CVD risk factors and MetS [42,43,44,45,46,47,48], such as physical activity or fitness, smoking, etc., were not under our consideration. Finally, the results in our study were attained from Jilin province, which might limit our ability to generalize the results to the rest of China.…”
Section: Discussionmentioning
confidence: 91%
“…Another study found that the average percent body fat in five LOPD patients was in the obese range at ~45% (23). Consequently, it appears that obesity is a significant issue in LOPD patients and is concerning for it will increase the risk of obesity-associated morbidities (34), especially when combined with low PA (35)(36)(37). Furthermore, the extra weight is a major issue in a patient with SM weakness and will further impair activities of daily living (ADL).…”
Section: Body Compositionmentioning
confidence: 99%
“…The fat but fit paradigm suggests that having high fitness may attenuate most of the adverse effects of obesity on all-cause and CVD morbidity and mortality. 16 , 17 , 18 , 19 , 20 , 21 , 22 Furthermore, overweight and even mild obesity may be associated with better survival, especially in older populations. 20 , 22 Together these findings raise the possibility of a disparate effect of fitness and fatness on risk factors for CVD as compared with CVD events and especially mortality in an older cohort.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Indeed, high fitness has been reported to attenuate most of the adverse effects of overweight and even mild obesity on all-cause and CVD mortality and morbidity. 7 , 8 , 16 , 17 , 18 , 19 , 20 , 21 Individuals who are fat but fit have lower mortality rates than lean but unfit individuals both in the general adult population 11 , 12 , 13 and in older adults. 10 , 14 , 22 However, whether high fitness can modify the deleterious association between body fatness and cardiometabolic risk factors has not been adequately addressed in older adults, and findings in the general population have been inconsistent.…”
mentioning
confidence: 99%